The interplay between the proteolytic, invasive, and adhesive domains of invadopodia and their roles in cancer invasion - Revach, Or-Yam (Landes Bioscience, 2014)
Invadopodia are actin-based protrusions of the plasma membrane that penetrate into the extracellular matrix (ECM), and enzymatically degrade it. Invadopodia and podosomes, often referred to, collectively, as “invadosomes,” are actin-based membrane protrusions that facilitate matrix remodeling and cell invasion across tissues, processes that occur under specific physiological conditions such as bone remodeling, as well as under pathological states such as bone, immune disorders, and cancer metastasis. In this review, we specifically focus on the functional architecture of invadopodia in cancer cells; we discuss here three functional domains of invadopodia responsible for the metalloproteinase-based degradation of the ECM, the cytoskeleton-based mechanical penetration into the matrix, and the integrin adhesome-based adhesion to the ECM. We will describe the structural and molecular organization of each domain and the cross-talk between them during the invasion process.